Simultaneous Design of PSS Parameters and SVC Control System by VURPSO Algorithm in Order to Increase Stability of the Power System - Esmaeel Ghaedi; Ghazanfar Shahgholian; Rahmat Allah Hooshmand (Majlesi Journal of Electrical Engineering, 2024)
In this paper, the multi-machine power system is simulated and in addition, VURPSO optimization algorithm is used to optimize the parameters of simultaneous controllers of Static Var Compensator (SVC) and power system stabilizer (PSS) in order that the power system stability increases. By SVC, the transferrable power in steady state can be increased and the voltage profile can be controlled along the line. The main role of PSS is damping the generator oscillations by controlling its stimulation by use of auxiliary supplementary signals. If it is assumed in this paper that a three phase short circuit fault with the ground has occurred in a four-machine power system, SVC and PSS simultaneous controllers are used to damp the oscillations and stabilize the system.